Infections and mortality in ICU patients undergoing continuous renal replacement therapy: a retrospective cohort study - Danica Quickfall; Ashley La; Jennifer Pisano; Patrick Costello; Samantha Gunning; Jay L. Koyner (BMC Nephrology)
Abstract Background Critically ill patients receiving continuous renal replacement therapy (CRRT) are at increased risk for multidrug-resistant infections and infection-related mortality. Altered pharmacokinetics in CRRT may contribute to inadequate antimicrobial exposure and therapeutic failure. However, limited data exist on infection burden and resistance patterns specific to this population. Methods We conducted a retrospective cohort study of ICU patients receiving continuous venovenous hemodialysis (CVVHD) at a tertiary academic center between May 2016 and April 2020. Patients were included if they received CRRT for ≥ 48 h, had at least one positive microbial culture, and received at least one antimicrobial of interest. Data were collected on infection sources, pathogens, resistance patterns, and mortality. Results Among 661 CRRT recipients, 394 (59.6%) had at least one positive culture. The most common infection sites were respiratory (69.0%), skin and soft tissue (53.8%), and intra-abdominal (38.8%). Intra-abdominal and bloodstream infections had the highest mortality (63.7% and 57.7%, respectively). Vancomycin-resistant E. faecium (83.3%), cefepime-resistant A. baumannii (100%), and P. aeruginosa with high β-lactam resistance were prominent. These resistance profiles diverged from general ICU trends. Conclusion ICU patients receiving CRRT experience high rates of multidrug-resistant infections and associated mortality. Tailored dosing strategies, including dual empiric coverage in select cases, and CRRT-specific antimicrobial stewardship are essential to improve outcomes in this high-risk population.